Prophylactic use of vacuum-assisted closure system for cannula sites: A case of extracorporeal biventricular assist devices for 295 days. Issue 2 (February 2022) - Takami, Yoshiyuki; Tanida, Shin-ichi; Hoshino, Naoki; Sakurai, Yusuke; Amano, Kentaro; Akita, Kiyotoshi; Hayashi, Ryosuke; Maekawa, Atsuo; Izawa, Hideo; Takagi, Yasushi
We report wound management using a vacuum-assisted closure (VAC) system for the cannula sites of extracorporeal biventricular assist devices (BiVADs) for 295 days in a 23-year old Chinese female patient with fulminant giant cell myocarditis, who finally underwent heart transplantation. When the cannula sites appeared necrotic 3 months after BiVADs placement, she received negative pressure wound therapy prophylactically for four cannula sites, using a VAC system for 3 months, followed by no infections. Such prophylactic VAC therapy, using the skin barrier paste usually used for the ostomy pouching system to create a flatter surface and airtightness, may be useful to avoid cannula site infections, which is still a fatal complication causing sepsis, especially in patients with extracorporeal BiVADs.